Effectiveness of Abdominal Massage with Effleurage Technique for Constipation - Yobel, Sosilo; Kristiani, Rina Budi (STIKES Adi Husada, 2024)
Constipation is a symptom, not a disease, the causes are improper diet, reduced fluid intake, lack of exercise, and certain medications. Constipation is characterized by defecating less than three times a week, and feces that are hard, dry, and difficult to expel, causing discomfort. One non-pharmacological therapy that can be used to treat constipation is abdominal massage with effleurage technique. The aim of this research was to analyze the effectiveness of abdominal massage using the effleurage technique against constipation in Dukuh Setro Village, Tambaksari District, Surabaya City. This research design uses a pre-experimental group pre-post test design, the research instrument uses an observation sheet, with a total of 31 respondents. The sampling technique used is simple random sampling. Data analysis used the McNemar statistical test. The results of the research before the abdominal massage were carried out with the effleurage technique all respondents (100%) experienced constipation after abdominal massage with the effleurage technique as many as 80.6% stated that they did not have constipation. The statistical test results obtained a significant p-value in the constipation category before and after abdominal massage with effleurage technique is p value = 0.000 with ɑ = < 0.05, this shows that abdominal massage with Effleurage technique is effective for treating constipation. Implications of abdominal massage research results with effleurage technique are One alternative action to treat constipation if done regularly and can become a new habit for adults who experience constipation.